(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Depression and anxiety are some of the common Psychiatric disorders that are prevalent in women and pose a considerable threat to the global public health. Objective: The objective of this study is to analyze the correlation between hormonal contraceptive use and the incidence of Psychiatric disorders in women. Study Design: A Retrospective Analysis Study. Duration and place of the study: Department of Psychiatry & GYNAE & OBS Mardan Medical Complex (MMC) Mardan from 6th March 2020 to 5th Sep 2021. Material and Methods: The participants of the study consisted of 100 women, 18-45 years of age, using different types of hormonal contraception containing Combined Oral and injectable Contraceptive Pills, Injections The participants received face-to-face interviews as well as administered questionnaires which aimed at identifying Psychiatric disorders, such as depression, anxiety, and Psychiatric swings. Psychiatric disorders related to contraceptive use were evaluated based on the data collected and compared to pre-contraceptive use. Results: The sample of the study was of 100 women between the age range of the 18-45 years with the mean age of 29.3 ± 7.2 years. Hormonal contraceptives involved oral tablets 65%, injections 35% . Hence, history of Psychiatric disorder was prevalent in 30% of patients before initiating hormonal contraception. 22% reported mild to moderate depressive symptoms before starting hormonal contraceptives and 18% reported mild to moderate anxiety symptoms. Further, none of the participants had a severe Psychiatric disorder, which can lead to hospitalization and other severe psychiatric interventions. Conclusion: The study’s results point out to hormonal contraceptives as contributing to Psychiatric disorder, as more than a third of the women reported new or worsening symptoms.